Cellulose‐Derived Carbon Fibers Produced via a Continuous Carbonization Process: Investigating Precursor Choice and Carbonization Conditions. Issue 22 (14th July 2016) - Byrne, Nolene; Setty, Mohan; Blight, Simon; Tadros, Ray; Ma, Yibo; Sixta, Herbert; Hummel, Michael
Abstract : Here, the carbonization of two Lyocell type regenerated cellulose fibres is reported. Commercially available Lyocell as well as the experimental Lyocell type fibre known as Ioncell‐F spun from the ionic liquid 1, 5‐diazabicyclo[4.3.0]non‐5‐ene‐1‐ium acetate ([DBNH]OAc) is investigated, which supports higher draw ratio and thus improves precursor mechanical properties. Lyocell fibres are known to have improved mechanical properties over other regenerated cellulose fibres and are therefore considered to be better carbon fibre precursor candidates. The Lyocell fibres used in this study are carbonized utilizing a scaled down identical replica of an in use carbon fibre line. The importance of this is the ability to assess the performance of the Lyocell fibres under more realistic continuous carbonization processing conditions. The tensile properties, morphology, and chemical composition of all fibres are determined. It is shown that by changing the carbonization temperature and atmosphere fibres with different mechanical properties and diameter can be produced. Elemental analysis confirms that each fibre has a carbon content of ≥90%. Abstract : New advances for cellulose carbon fibres : Here we report on the development of carbon fibres using a novel technical grade cellulosic fibre achieved by continuous carbonization process. A tensile strength of 1.4 GPa is achieved at maximum heating temperature of 1400 °C. Differences in properties are noted as result of different carbonisation parameters.